DIOGENES THE CYNIC IN THE LITERARY REPUBLIC - García López, Jorge (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This essay wishes to study the break of 16th-century Humanism as it occurs in Saavedra’s work and its consequence –the evaluation of experience, of what is immediate, historical, and personal. In this context, the appropriation of cynical experience attains a new meaning beyond neo-stoic models and, of course, in contraposition to the control of Spanish neo-scholastics.
Keywords: Neo-stoicism; Cynicism; Scepticism; scholastics; School of Salamanca